Family Education Efforts in Overcoming Juvenile Delinquency - Ahmad Putra; Yulia Fitria; Bima Prasetya (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
This article discusses the education that families provide to children in overcoming various forms of delinquency carried out by juveniles in Karang Tangah village, West Sumatra. It is believed that the family is the main pillar that shapes the personality and attitude of a child. Thus, it really needs attention and primary teaching from the family so that children avoid the influence of technological advances that could have pushed every child (juveniles) involved in various forms of mischief. Along with the times and technology, without us knowing so much it is heard that children or juveniles are involved in mischief’s they are not supposed to do that will only harm themselves. Therefore, this research will describe the various forms of delinquency that juveniles do and of course, there are efforts and efforts of parents in looking after their children. It is hoped that parents can take care of and educate their children well.